PENGARUH PEMBELAJARAN KONSTRUKTIVISME DILENGKAPI MIND MAP TERHADAP HASIL BELAJAR MAHASISWA DI APIKES IRIS PADANG - Rahmi Septia Sari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The Study aims to determine the effect of applying the learning model of kontegitivism which is equipped with a mind map of activities on the learning outcomes of students. This research is a quasi-experimental study (Quasi Experiment). The population of this research is the first-rate Apikes Iris students in the Anatomi Physiology course in the academic year 2019/2020. Whereas the sample of this study was Apikes Iris level one local B students as an experimental class treated by applying the Constructivism learning model equipped with mind maps and Local A as a control class treated with conventional models. The instruments used in this study were in the form of knowledge test questions, and attitudes and skills observation sheets. Data analysis in this study used the t-test for knowledge competency and Mann Whitney U test, for attitude and skill competencies. The results showed that the average value of the learning competence of experimental class students was 80.03 better than the control class students who were only 73.91. It can be concluded that the application of constructivism learning models equipped with mind maps has an effect on improving student learning outcomes.